Approach to Radiculopathy - Mustafa, Rafid; Kissoon, Narayan R. (Seminars in Neurology, 2021)
Low back pain and neck pain, often with associated radiculopathy, are two of the most common reasons for referral to the outpatient neurology clinic. A thorough clinical evaluation remains paramount in establishing an accurate diagnosis and subsequently an appropriate treatment plan. In this article, we review anatomic considerations for spondylotic radiculopathy; outline the clinical approach for the evaluation of these patients, including discussion of electrodiagnostic and imaging modalities; and address treatment options based on a stratified treatment approach.
Keywords: radiculopathy; spondylosis; neck pain; low back pain